Property public auction practice in Malaysia / Norfaizie Siran - Siran, Norfaizie (2012)
Public auction properties are actions when the borrowers default, the lender who is called the chargee, is entitled to foreclose the charge. This means taking the permitted steps provided for in the National Land Code to have the land auctioned off, pay itself the money owed and hand over the difference, if any, to the land owner, whether he is the borrower or a third party. Foreclosure is a process that allows a lender to recover the amount owed on a defaulted loan by selling or taking ownership of the property securing the loan. The foreclosure process begins when a borrower/owner defaults on loan payments and the lender files a public default notice. Therefore, this study has been developed with the aim to identify the objective related to public auction in Malaysia. The study was conducted through structured interview with licensed auctioneer, banker, land administrator and registrar of the court and also through postal questionnaires. The property public auction practice in Malaysia usually conducted by three bodies, Financial Institution, Land Office and Court and each body have their own way procedures and process to dispose the properties auction. Furthermore, each body has their category of land to disposed properties under public auction. This academic to help the layman and licensed auctioneer conduct public property auction. In addition, auctions are commonly associated with reserve prices that are lower than market value. There is no certainty that the reserve price can be secured as others would be bidding for the same property in a popular location.